2020
DOI: 10.3390/jcs4010020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbon/Carbon Nanotube Composites as Electrocatalysts for the Oxygen Reduction Reaction

Abstract: The oxygen reduction reaction is an essential reaction in several energy conversion devices such as fuel cells and batteries. So far, the best performance is obtained by using platinum-based electrocatalysts, which make the devices really expensive, and thus, new and more affordable materials should be designed. Biomass-derived carbons were prepared by hydrothermal carbonization in the presence of carbon nanotubes with different oxygen surface functionalities to evaluate their effect on the final properties. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…These spheres were probably produced from glucose through hydrothermal treatment under the conditions used. 42,48 A similar effect was also obtained by Morais et al 50 Based on the textural analyses, EA and SEM results, it can be concluded that two types of mechanisms were employed in the present work to facilitate the functionalization of CNTs with sulfur. The first one was the creation of the new active graphene edges during ball-milling of CNTs, as evidenced by the breaking of large CNT aggregates (compare SEM micrographs in Fig.…”
Section: Catalysis Science and Technology Papersupporting
confidence: 87%
“…These spheres were probably produced from glucose through hydrothermal treatment under the conditions used. 42,48 A similar effect was also obtained by Morais et al 50 Based on the textural analyses, EA and SEM results, it can be concluded that two types of mechanisms were employed in the present work to facilitate the functionalization of CNTs with sulfur. The first one was the creation of the new active graphene edges during ball-milling of CNTs, as evidenced by the breaking of large CNT aggregates (compare SEM micrographs in Fig.…”
Section: Catalysis Science and Technology Papersupporting
confidence: 87%
“…Removal of lead nitrate (200 ppm) had been determined by atomic absorption spectroscopy, after incubation at room temperature with 16 g/L of Mg-doped NiO and Mg doped NiO\MWCNTs nanocomposites within 24 h. The percentage of lead nitrate was removed by using the synthesized nanoparticles as shown in Figure (7). The highest percentage of lead removal from watery phase were 62 and 43 performed in the presence of Mg-doped NiO NPs and Mg doped NiO\MWCNTs nanocomposite, respectively, with signi cant analyses of P≤ 0.001 observed in all treatments.…”
Section: Biological Treatmentsmentioning
confidence: 99%
“…The MWCNTs also play an important role in preparing nanocomposites and treating water pollution [3][4][5][6]. The MWCNTs are produced from various methods including arc chemical vapor deposition (CVD) [6], hydrothermal processes [7], discharge [8], laser ablation [9], etc. To improve the performance of MWCNTs, the decorating them with metal oxides has been widely used due to good merits such as thermal stability and, high mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…2d, among which quaternary-N and pyridinic-N are very likely to be benecial to the ORR catalytic process. [25][26][27] The contents of various N in samples according to the intensity of each peak deconvolution conducted by the tting program (Casa XPS Version 2.3.16 Pre-rel) are shown in Table 2, in which, quaternary N and pyridinic N for NCoNC sample account for 64.13% of the total N signicantly higher than those of CoNC (48.85%) and NCoC (53.67%).…”
Section: Characterization Of As-prepared Samplesmentioning
confidence: 99%